Komik; Sebentuk Budaya Kreatif Perkembangan Sastra - Ulum Janah (Faculty of Letters Universitas Balikpapan, 2021)
The development literature is inseparable from the medium used. Human creativity to package his work, in this case with regard to literature is a form of culture that also will not come off with the medium. One of the media used to pack the literary work is a visual medium. Furthermore, the literature is termed as